When Northern Swahili Met Southern Somali - Nurse, Derek (My University, 2019)
Some twelve hundred years an incipient Northern Swahili community had moved up the Kenya coast as far as the Lamu Archipelago, where it came in contact with one or more Somali communities and the isolate Dahalo community. This paper initially uses phonological innovations in the early Swahili dialect to establish the general fact of contact, and then attempts to use sets of loanwords to identify the Somali source. Due to inadequate sources, it has proved difficult to identify the source(s) with certainty but initial contact with Tunni over some centuries, followed by later contact with Garre, is the most plausible explanation. The Tunni and Garre later exited, the latter leaving strong traces behind in Boni.
Keywords: Northern Swahili; southern Somali; community